A systematic review of Streptococcus Mutans and Veillonellae species interactions in dental caries progression: Positive or Negative impact? [version 1; peer review: 1 approved, 2 approved with reservations, 1 not approved] - Faizul Hasan; Prawati Nuraini; Ariadna Adisattya Djais; Ervina Restiwulan Winoto; Tantiana Tantiana; Rini Devijanti Ridwan; Juni Handajani; Rajesh Ramasamy; Silvia Anitasari; Hendrik Setia Budi (F1000Research)
Background The interaction between Streptococcus mutans (S. mutans) and Veillonella species (Veillonella spp.) is unclear. This study aims to investigate the interaction between S. mutans and Veillonella spp. on caries development using systematic review. Methods This systematic review was accorded to the guideline of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses. Three electronic databases, namely PubMed, Embase, and the Cochrane library, were used to conduct a systematic search for eligible studies from their inception until July 18, 2023. PROSPERO registration number was No. CRD42023445968. Results We initially identified 4,774 articles. After eliminating duplicates and irrelevant articles, 11 studies met the inclusion criteria. The studies revealed important aspects of the relationship between S. mutans and Veillonellae spp. in dental caries. One significant finding is that Veillonellae spp. can affect the acid production capacity of S. mutans. Some studies indicate that Veillonellae spp. can inhibit the acid production by S. mutans, potentially reducing the cariogenic process. Another aspect is the competition for substrates. Veillonellae spp. utilize lactic acid, which is a by product of S. mutans metabolism, as a source of carbon. This metabolic interaction may decrease the availability of lactic acid for S. mutans, potentially influencing its cariogenic potential. Conclusions This systematic review highlights the emerging evidence on the interaction between S. mutans and Veillonellae spp. in dental caries. The findings suggest that Veillonellae spp. can modulate the acid production, and substrate competition of S. mutans, potentially influencing the cariogenic process.